Zirconium alloy cast ingot, high-quality Zr-Sn-Nb alloy strip for nuclear power and preparation method and application of Zr-Sn-Nb alloy strip

By adopting the direct hot rolling process of large zirconium alloy slabs, the problems of low production efficiency and poor weld area performance of existing zirconium alloy strips are solved, and higher production efficiency and better strip performance are achieved.

CN119592844APending Publication Date: 2025-03-11STATE NUCLEAR BAOTI ZIRCONIUM IND CO +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411676400.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The production efficiency of existing zirconium alloy strips is low, and there are differences in the weld area and the structure performance of the base material, resulting in poor dimensional uniformity and belt type consistency, and there is a risk of easy breakage of the belt.

Method used

The direct hot rolling process of large zirconium alloy slabs is adopted to cancel the process of hot rolling, surface treatment, cold rolling of veneer plates and welding of veneer plates. The deformation amount is increased through the hot rolling technology of large slabs, weaken the base surface texture, improve the lateral texture, and eliminate the adverse effects of the weld area.

Benefits of technology

The production efficiency of zirconium alloy strips is improved by about 30%, the effective utilization rate of the strips is enhanced by about 10%, the structural performance and punching performance of the finished strips are improved, and the risk of breaking the strips is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592844A_ABST
    Figure CN119592844A_ABST
Patent Text Reader

Abstract

The invention discloses a zirconium alloy cast ingot, a high-quality Zr-Sn-Nb alloy strip for nuclear power and a preparation method and application of the high-quality Zr-Sn-Nb alloy strip. According to the method, a direct hot rolling coiling process of the zirconium alloy large plate blank is adopted, the technical parameters of hot continuous rolling of the large plate blank, namely the plate blank thickness, the hot rolling temperature, the rolling speed and the pass deformation, are mainly controlled, and the key performance such as zirconium alloy corrosion is guaranteed; according to the process, the deformation amount is increased, the basal texture is weakened, the transverse texture is improved, and the structure performance of the finished strip is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and in particular to a zirconium alloy ingot, a high-quality Zr-Sn-Nb alloy strip for nuclear power, and a preparation method and application thereof. Background Art

[0002] Zirconium has excellent nuclear properties and is a key material for manufacturing pressurized water reactor nuclear fuel assemblies. It is widely used in nuclear fuel elements such as cladding tubes, pressure tubes, and grids. As nuclear reactors continue to develop towards high fuel consumption, high thermal efficiency, and high safety and reliability, more stringent requirements are placed on zirconium alloy materials. In order to meet the development needs of the third-generation nuclear power, two new zirconium alloys, SZA-4 (nominal composition Zr-0.8Sn-0.25Nb-0.35Fe-0.1Cr-0.05Ge) and SZA-6 (nominal composition Zr-0.5Sn-0.5Nb-0.3Fe-0.015Si), have been developed, which have better corrosion resistance and creep resistance, and meet the use requirements of the third-generation nuclear pressurized water reactor fuel assemblies.

[0003] Zirconium alloy strip is an essential material for manufacturing nuclear fuel assembly grids. Its stamping performance, corrosion performance, creep performance, and fatigue performance play a decisive role in the dimensional stability and service reliability of nuclear fuel assemblies. Due to the hexagonal crystal structure of zirconium alloy α phase, the number of slip systems activated during plastic deformation is limited, and the deformation capacity at low temperature is poor. Therefore, the existing nuclear-grade zirconium alloy strip processing technology is as follows: first, the billet is cut into a suitable size, and after homogenization treatment, a small slab (slab length 600mm-1200mm) single plate is used for hot rolling. In order to prevent the plate from cracking, the deformation of each pass is generally controlled between 15% and 25%. After intermediate annealing and cold working to a certain thickness, multiple single plates are welded into coils, and finally processed into finished strips through cold rolling and heat treatment of strip coils. Since the deformation of a single plate rolling is small, multiple rolling passes are required to obtain the final size, and in order to maintain the appropriate rolling temperature, multiple heating passes are required between passes, so the production efficiency of zirconium alloy strips is very low. In addition, there are differences in the microstructure and properties of the weld area and the parent material. Affected by the weld, the strip cold rolling process has problems with dimensional uniformity and poor strip consistency, and there is a risk of easy strip breakage. The effective length between welds of the finished strip is 15 meters to 30 meters, the strip "progressive die" punching continuity is poor, and the strip punching utilization rate is less than 70%. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0005] To this end, embodiments of the present invention provide a zirconium alloy ingot, a high-quality Zr—Sn—Nb alloy strip for nuclear power, and a preparation method and application thereof.

[0006] In a first aspect, the present invention provides a zirconium alloy ingot, wherein, by mass content, the Sn content of the zirconium alloy ingot is 0.5% to 1.0%, the Nb content is 0.2% to 1.1%, the O content is 0.08% to 0.14%, the Fe content is 0.2% to 0.5%, and the Si content is 0.01% to 0.02%.

[0007] In a second aspect, the present invention provides a method for preparing a high-quality Zr-Sn-Nb alloy strip for nuclear power, using the zirconium alloy ingot provided in the first aspect of the present invention, comprising the following steps:

[0008] (a) processing a zirconium alloy ingot into a slab by free forging;

[0009] (b) directly β-phase quenching the slab and removing the surface oxide scale, and then hot-rolling the slab to a continuous length of more than 40 m to obtain a hot-rolled slab;

[0010] (c) bending the hot-rolled slab into a coil and subjecting it to homogenization treatment until the grain size of the coil is above 8.0 and the transverse texture factor is above 0.35;

[0011] (d) mechanically polishing and chemically polishing the tape coil obtained in step (c) to a surface roughness of less than 1.6 μm, and bending the tape coil into a coil at room temperature;

[0012] (e) unwinding the strip coil obtained in (d), cold rolling it to obtain a seamless strip, and degreasing and annealing it to obtain a finished strip.

[0013] Furthermore, in step (a), the free forging adopts a two-fire forging process, the forging temperature is 850-1100° C., and the holding time is 60-240 min.

[0014] Furthermore, in step (a), the slab has a thickness of 80 to 150 mm and a length of 2000 to 6000 mm.

[0015] Furthermore, in step (b), the temperature of the β-phase quenching is 50-120° C. higher than the β-phase transformation temperature of the zirconium alloy.

[0016] Furthermore, in step (b), hot rolling is carried out by a hot rolling mill, the hot rolling temperature is 550-700° C., the hot rolling deformation is 75%-95%, and the slab is hot rolled once through 8-15 passes to a thickness of 3-7 mm.

[0017] Furthermore, in step (c), the homogenization treatment is carried out at 580-650° C. for 2-6 hours, and the temperature of the homogenization treatment is lower than the hot rolling temperature.

[0018] Furthermore, in step (e), the cold rolling deformation amount during the cold rolling process is 60% to 95%, the rolling speed is 30 to 120 m / min, and the pass deformation amount is 5% to 20%.

[0019] Furthermore, in step (e), the grain size of the finished strip is above level 10.0, and the transverse texture factor is above 0.30.

[0020] In a third aspect, the present invention proposes a high-quality Zr—Sn—Nb alloy strip for nuclear power prepared by the method proposed in the second aspect.

[0021] In a fourth aspect, the present invention proposes the use of the high-quality Zr—Sn—Nb alloy strip prepared by the method proposed in the second aspect or the high-quality Zr—Sn—Nb alloy strip proposed in the third aspect in nuclear fuel assemblies.

[0022] Compared with the prior art, the beneficial effects of the present invention are:

[0023] The Zr-Sn-Nb alloy strip material of the present invention adopts a large slab direct hot rolling coiling process, which eliminates the single plate hot rolling, surface treatment, single plate cold rolling and welding coiling steps in the existing process, and the production efficiency can be improved by about 30%, while reducing weld waste and the effective utilization rate of the strip material can be increased by 10%.

[0024] The present invention adopts a process for directly hot rolling large zirconium alloy slabs into coils, mainly controlling the technical parameters of hot continuous rolling of large slabs, namely, slab thickness, hot rolling temperature, rolling speed and pass deformation, thereby ensuring key properties such as zirconium alloy corrosion; the process increases the deformation, weakens the base surface texture, improves the transverse texture, and improves the microstructure and properties of the finished strip.

[0025] The present invention eliminates the adverse effects of the weld area on the cold rolling deformation of the strip by adopting seamless rolling, eliminates the risk of strip breakage, and improves the rolling stability of the finished zirconium alloy strip and the control accuracy of the strip shape and size.

[0026] The raw material zirconium alloy ingot used in the present invention has a Sn content of 0.5% to 1.0%, a Nb content of 0.2% to 1.1%, an O content of 0.08% to 0.14%, a Fe content of 0.2% to 0.5%, and a Si content of 0.01% to 0.02%, so that the alloy has excellent corrosion resistance, effectively inhibits the harmful effects of elements such as N, C, Al, and Ti, and ensures good comprehensive mechanical properties at the same time. The finished product has excellent stamping performance and meets the application requirements of structural materials under in-pile irradiation conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0028] Figure 1 This is a flow chart of the method for preparing high-quality Zr-Sn-Nb alloy strip for nuclear power of the present invention;

[0029] Figure 2 This is the metallographic structure diagram of the hot-rolled annealed coil according to Example 1 of the present invention;

[0030] Figure 3 This is the metallographic structure diagram of the finished strip of Example 1 of the present invention;

[0031] Figure 4 This is the texture pole figure of the hot-rolled annealed coil according to Example 1 of the present invention;

[0032] Figure 5 This is the texture pole figure of the finished strip of Example 1 of the present invention;

[0033] Figure 6 This is the texture pole figure of the finished strip of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0034] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0035] like Figure 1 As shown, the method for preparing high-quality Zr-Sn-Nb alloy strip for nuclear power of the present invention comprises the following steps:

[0036] (a) processing a zirconium alloy ingot into a slab by free forging, wherein, by weight, the zirconium alloy ingot has a Sn content of 0.5% to 1.0%, a Nb content of 0.2% to 1.1%, an O content of 0.08% to 0.14%, a Fe content of 0.2% to 0.5%, and a Si content of 0.01% to 0.02%;

[0037] (b) directly β-phase quenching the slab and removing the surface oxide scale, and then hot-rolling the slab to a continuous length of more than 40 m to obtain a hot-rolled slab;

[0038] (c) bending the hot-rolled slab into a coil and subjecting it to homogenization treatment until the grain size of the coil is above 8.0 and the transverse texture factor is above 0.35;

[0039] (d) mechanically polishing and chemically polishing the tape coil obtained in step (c) to a surface roughness of less than 1.6 μm, and bending the tape coil into a coil at room temperature;

[0040] (e) unwinding the strip coil obtained in (d), cold rolling it to obtain a seamless strip, and degreasing and annealing it to obtain a finished strip.

[0041] Wherein, step (a) adopts a two-fire forging process to process the zirconium alloy ingot into a slab by free forging, so as to improve the zirconium alloy structure and enhance its processing performance.

[0042] The forging temperature is 850-1100°C, and the holding time is 60-240min. The forging temperature can be 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C or any two values ​​in the range. At the appropriate forging temperature, the deformation plasticity is good and the forging quality is high; if the forging temperature is too high, the gas pollution is serious, the alloy plasticity decreases, and the organization deteriorates, which makes the forging quality worse; if the forging temperature is too low, the deformation resistance is large, which makes deformation difficult and prone to crack defects. After forging, the thickness of the slab is 80-150mm and the length is 2000-6000mm.

[0043] The raw material zirconium alloy ingot required for forging has a Sn content of 0.5% to 1.0%, a Nb content of 0.2% to 1.1%, an O content of 0.08% to 0.14%, a Fe content of 0.2% to 0.5%, and a Si content of 0.01% to 0.02%, which makes the alloy have excellent corrosion resistance, effectively inhibits the harmful effects of elements such as N, C, Al, and Ti, and ensures good comprehensive mechanical properties. The finished product has excellent stamping performance and meets the application requirements of structural materials under in-pile irradiation conditions.

[0044] When the Sn content exceeds the range, the Sn content is too low or too high, it will affect the corrosion resistance of the alloy. In addition, a low Sn content will also reduce the strength of the material.

[0045] When the Nb content exceeds the range, the low Nb content will affect the corrosion resistance of the alloy, Nb has a more obvious strengthening effect, and the high Nb content increases the deformation resistance, thereby increasing the hot working temperature.

[0046] When the O content exceeds the range, the mechanical strength will decrease due to the low O content, while the processing performance of the material will deteriorate due to the high O content. The plastic deformation will easily cause defects such as edge cracks, and it will also affect the stamping performance of the finished strip.

[0047] When the Fe content exceeds the range, the low Fe content will reduce the mechanical strength, while the high Fe content will significantly reduce the plasticity and deteriorate the processing performance.

[0048] When the Si content exceeds the range, the low Si content reduces the mechanical strength, while the high Si content has a certain effect on the impact toughness.

[0049] In step (b), the slab obtained after forging is directly subjected to β-phase quenching without being shortened to homogenize the slab. The temperature of the β-phase quenching is 50 to 120°C higher than the (α+β) / β phase transformation temperature of the zirconium alloy, so that all the second phase particles are completely dissolved, and a quenched structure with uniform structure and component distribution is obtained. The specific process is to keep the temperature at the β-phase quenching temperature in an atmospheric environment for 90 to 240 minutes, and then water quench.

[0050] The process of removing the surface oxide scale is as follows: heating the slab obtained by β-phase quenching treatment to 550-700°C, applying pressure to flatten the plate shape, and removing the oxide scale on the surface of the slab by mechanical processing to obtain a clean surface and the size required for the next process. Among them, the mechanical processing to remove the oxide scale on the surface of the slab can be carried out by planing and washing.

[0051] The hot rolling process is as follows: hot rolling is performed by a hot rolling mill, the hot rolling temperature is 550-700°C, the hot rolling deformation is 75%-95%, and the slab is hot rolled once through 8-15 passes to a thickness of 3-7 mm, and the continuous length is more than 40 m to obtain a hot rolled slab. The hot rolling mill has a plurality of continuously arranged stands, so that the slab can be continuously rolled through multiple passes.

[0052] In step (c), the hot-rolled slab is coiled at a temperature of 100 to 400°C to ensure that the coil has a good tower shape, which is convenient for transfer and subsequent processing. The process of homogenizing the coil is at a temperature of 580 to 650°C for 2 to 6 hours, and the temperature of the homogenization treatment is lower than the aforementioned hot rolling temperature, so that the structure is uniform and a dispersed precipitation phase is obtained. The homogenization treatment is performed until the grain size of the coil is above 8.0 and the transverse texture factor is above 0.35. The homogenization treatment is annealed in the atmosphere to recrystallize the material structure and restore the plasticity required for subsequent processing deformation.

[0053] In some embodiments, the annealing process is heated using a resistance furnace.

[0054] In step (d), the process of mechanical polishing and chemical polishing is as follows: after the zirconium alloy strip coil obtained in step (c) is flattened, the surface of the strip coil is first treated by sandblasting or steel shot blasting, and then mechanically polished to remove surface oxide scale, cracks and other defects that affect subsequent processing, and then continuously immersed in a mixture of HNO3, HF, and deionized water. Chemical polishing makes the corrosion more uniform. After mechanical polishing and chemical polishing, the surface roughness Ra of the strip coil does not exceed 1.6μm, and it is rolled into a coil at room temperature.

[0055] In step (e), the cold rolling process is: the zirconium alloy obtained in step (d) is unrolled and cold rolled, the cold rolling deformation is 60% to 95%, the rolling speed is 30 to 120 m / min, the pass deformation is 5% to 20%, and a weld-free strip with the required size and surface of the finished pass deformation is obtained. It can be understood that during the cold rolling process, if the thickness of the strip does not change before and after rolling, annealing at 540 to 650°C is performed as needed to restore its processing plasticity. Degreasing is to soak and rinse the strip with alkali solution; annealing is to perform finished product annealing at 560 to 650°C. The grain size of the finished strip finally obtained is above 10.0 level, and the transverse texture factor is above 0.30.

[0056] The high-quality Zr-Sn-Nb alloy strip for nuclear power prepared by the present invention can be used in the preparation of nuclear fuel components.

[0057] The present invention is specifically described below in conjunction with embodiments.

[0058] Example 1

[0059] S1: The ingot is free forged into a slab by a two-fire forging process to improve the structure and processing performance. The forging temperature is 1050°C and the holding time is 180 minutes. The slab after forging has a thickness of 120 mm and a length of 4000 mm. The zirconium alloy ingot has a Sn content of 0.5%, a Nb content of 0.5%, an O content of 0.13%, a Fe content of 0.3%, and a Si content of 0.015% by mass.

[0060] S2: The slab obtained in S1 is not cut short, but directly subjected to β-phase quenching for homogenization treatment, the homogenization treatment temperature is 1050°C, and it is kept warm for 180 minutes in an atmospheric environment, and then water quenched.

[0061] S3: The slab treated in S2 is heated to 600°C, pressure is applied to flatten the plate shape, and the oxide scale on the surface of the slab is removed by mechanical processing. The thickness of the slab after treatment is 110 mm.

[0062] S4: The slab obtained in S3 is hot rolled by a hot rolling mill, with a hot rolling temperature of 598° C., a hot rolling deformation of 95%, and 12 passes of hot rolling to a thickness of 5 mm, with a continuous length of about 60 m.

[0063] S5: The hot-rolled sheet obtained in S4 is rolled into a coil at 300°C, and the coil has a good coil tower shape.

[0064] S6: The zirconium alloy coil obtained in S5 is homogenized at a temperature of 600°C and a holding time of 3 hours. The coil has a fine and uniform structure, a grain size of 11.0, and a transverse texture factor of 0.385.

[0065] S7: After the strip coil obtained in S6 is flattened, it is first subjected to surface treatment by shot peening, mechanical polishing, etc. to remove defects such as oxide scale and cracks on the surface of the strip coil that affect subsequent processing, and then continuous immersion chemical polishing is performed. The surface roughness Ra of the strip coil after surface treatment should be 1.2μm, and it is rolled into a coil at room temperature.

[0066] S8: The zirconium alloy strip coil treated in S7 is unrolled and cold rolled, with a cold rolling deformation of 80% and a rolling speed of 60 m / min. An annealing at 580° C. is performed in the middle to restore the processing plasticity, so as to obtain a weld-free strip with the size and surface required for the finished product deformation.

[0067] S9: The strip obtained in S8 is continuously degreased and annealed at 580°C to obtain the required structure and performance of the finished strip. The finished strip has fine and uniform structure, a grain size of 12.0, and a transverse texture factor of 0.311.

[0068] Example 2

[0069] S1: The ingot is free forged into a slab by a two-fire forging process to improve the structure and processing performance. The forging temperature is 1070°C and the holding time is 180min. The thickness of the slab after forging is 110mm and the length is 6000mm. The Sn content is 0.8%, the Nb content is 0.25%, the O content is 0.11%, the Fe content is 0.25%, and the Si content is 0.02% by mass.

[0070] S2: The slab obtained in S1 is not cut short, but directly subjected to β-phase quenching for homogenization treatment. The homogenization treatment temperature is 1070°C, and the slab is kept warm for 120 minutes in an atmospheric environment, and then water quenched.

[0071] S3: The slab treated in S2 is heated to 590°C, pressure is applied to flatten the plate shape, and the oxide scale on the surface of the slab is removed by mechanical processing. The thickness of the slab after treatment is 100 mm.

[0072] S4: The slab obtained in S3 is hot rolled by a hot rolling mill, with a hot rolling temperature of 590° C. and a hot rolling deformation of 96%. The slab is hot rolled once through 14 passes to a thickness of 4 mm and a continuous length of about 150 m.

[0073] S5: The hot-rolled sheet obtained in S4 is rolled into a coil at 200°C, and the coil has a good coil tower shape.

[0074] S6: The zirconium alloy coil obtained in S5 is homogenized at a temperature of 590°C and a holding time of 4 hours. The coil has a fine and uniform structure, a grain size of 10.5, and a transverse texture factor of 0.366.

[0075] S7: After the strip coil obtained in S6 is flattened, it is first subjected to surface treatment by shot peening, mechanical polishing, etc. to remove defects such as oxide scale and cracks on the surface of the strip coil that affect subsequent processing, and then continuous immersion chemical polishing is performed. The surface roughness Ra of the strip coil after surface treatment should be 1.2μm, and it is rolled into a coil at room temperature.

[0076] S8: The zirconium alloy coil treated in S7 is unrolled and cold rolled, with a cold rolling deformation of 85% and a rolling speed of 55 m / min. An annealing at 590° C. is performed in the middle to restore the processing plasticity, so as to obtain a weld-free strip with the size and surface required for the finished product deformation.

[0077] S9: The strip obtained in S8 is continuously degreased and annealed at 590°C to obtain the required structure and performance of the finished strip. The finished strip has fine and uniform structure, a grain size of 11.5, and a transverse texture factor of 0.315.

[0078] Example 3

[0079] S1: The ingot is free forged into a slab by a two-fire forging process to improve the structure and processing performance. The forging temperature is 1030°C and the holding time is 120 minutes. The thickness of the slab after forging is 90 mm and the length is 3000 mm. In terms of mass content, the Sn content of the zirconium alloy ingot is 0.7%, the Nb content is 1.0%, the O content is 0.12%, the Fe content is 0.5%, and the Si content is 0.01%.

[0080] S2: The slab obtained in S1 is not cut short, but directly subjected to β-phase quenching for homogenization treatment. The homogenization treatment temperature is 1030°C, and the slab is kept warm for 90 minutes in an atmospheric environment, and then water quenched.

[0081] S3: The slab treated in S2 is heated to 580°C, pressure is applied to flatten the plate shape, and the oxide scale on the surface of the slab is removed by mechanical processing. The thickness of the slab after treatment is 80mm.

[0082] S4: The slab obtained in S3 is hot rolled by a hot rolling mill, with a hot rolling temperature of 580° C., a hot rolling deformation of 96%, and 14 passes of hot rolling to a thickness of 3 mm, with a continuous length of about 80 m.

[0083] S5: The hot-rolled sheet obtained in S4 is rolled into a coil at 350°C, and the coil has a good coil tower shape.

[0084] S6: The zirconium alloy coil obtained in S5 is homogenized at a temperature of 580°C and a holding time of 3 hours. The coil has a fine and uniform structure, a grain size of 11.0, and a transverse texture factor of 0.356.

[0085] S7: After the strip coil obtained in S6 is flattened, it is first subjected to surface treatment by shot peening, mechanical polishing, etc. to remove defects such as oxide scale and cracks on the surface of the strip coil that affect subsequent processing, and then continuous immersion chemical polishing is performed. The surface roughness Ra of the strip coil after surface treatment should be 1.2μm, and it is rolled into a coil at room temperature.

[0086] S8: The zirconium alloy strip coil treated in S7 is unrolled and cold rolled, with a cold rolling deformation of 85% and a rolling speed of 80 m / min. An annealing at 580° C. is performed in the middle to restore the processing plasticity, so as to obtain a weld-free strip with the size and surface required for the finished product deformation.

[0087] S9: The strip obtained in S8 is continuously degreased and annealed at 580°C to obtain the required structure and performance of the finished strip. The finished strip has fine and uniform structure, a grain size of 11.5, and a transverse texture factor of 0.314.

[0088] Comparative Example 1

[0089] S1: The ingot is free forged into a slab by a two-fire forging process to improve the structure and processing performance. The forging temperature is 1050°C and the holding time is 180 minutes. The thickness of the slab after forging is 110 mm and the length is 3000 mm. The zirconium alloy ingot has a Sn content of 0.7%, a Nb content of 1.0%, an O content of 0.11%, a Fe content of 0.3%, and a Si content of 0.015% by mass.

[0090] S2: The slab obtained in S1 is cut into pieces with a length of 1000 mm using a sawing machine, and is subjected to β-phase quenching for homogenization treatment at a homogenization temperature of 1050° C. The slab is kept warm for 90 minutes in an atmospheric environment, and then water quenched.

[0091] S3: The slab treated in S2 is subjected to mechanical processing to remove the oxide scale on the surface of the slab, and the thickness of the slab after treatment is 100 mm.

[0092] S4: The slab obtained in S3 is hot rolled in two passes using a four-roll reversible hot rolling mill. The first pass is hot rolled at a heating temperature of 580°C, with a hot rolling deformation of 80%, and rolled to a thickness of 20 mm after 10 passes. The 20 mm slab rolled in the first pass is surface treated by sandblasting, mechanical polishing, etc. Each slab is cut into pieces of 1000 mm in length using a shearing machine, and the prepared 1000 mm slabs are heated and rolled in the second pass; the second pass is hot rolled at a heating temperature of 580°C, with a hot rolling deformation of 80%, and rolled to a thickness of 3.5 mm after 10 passes.

[0093] S5: The hot-rolled plate obtained in S4 is homogenized at a temperature of 580° C. for a holding time of 1.5 h. Sandblasting, mechanical polishing, pickling, etc. are used for surface treatment to remove defects such as oxide scale and cracks on the surface of the coil that affect subsequent processing. Each plate is cut into pieces with a length of 1000 mm using a shearing machine.

[0094] S6: The zirconium alloy plate obtained in S5 is subjected to intermediate cold rolling by a four-roll reversible cold rolling unit, with a cold rolling deformation of 66%. After degreasing, finishing and trimming, the plates are butt-welded into coils in pairs by argon arc welding. The coils are annealed in a vacuum annealing furnace to restore plasticity. The annealing temperature is 580°C and the holding time is 2h.

[0095] S7: The zirconium alloy strip coil with weld after S6 treatment is uncoiled and cold rolled, with a cold rolling deformation of 80% and a rolling speed of 30m / min. An annealing at 580°C is performed in the middle to restore the processing plasticity, and the strip with the required size and surface of the finished product is obtained. The weld area and the range of 100mm on both sides are unacceptable areas, and the effective length of the strip between welds does not exceed 30m.

[0096] S9: The strip obtained in S8 is continuously degreased and annealed at 580°C to obtain the required structure and performance of the finished strip. The finished strip has fine and uniform structure, a grain size of 11.5, and a transverse texture factor of 0.238.

[0097] Comparative Example 2

[0098] The difference from Example 1 is that the content of Sn in the zirconium alloy ingot is 0.25%, the content of Nb is 0.5%, the content of O is 0.11%, the content of Fe is 0.3%, and the content of Si is 0.015%.

[0099] Comparative Example 3

[0100] The difference from Example 1 is that the content of Sn in the zirconium alloy ingot is 0.5%, the content of Nb is 0.1%, the content of O is 0.11%, the content of Fe is 0.3%, and the content of Si is 0.015%.

[0101] Comparative Example 4

[0102] The difference from Example 1 is that the content of Sn in the zirconium alloy ingot is 0.5%, the content of Nb is 0.5%, the content of O is 0.15%, the content of Fe is 0.3%, and the content of Si is 0.015%.

[0103] Comparative Example 5

[0104] The difference from Example 1 is that the content of Sn in the zirconium alloy ingot is 0.5%, the content of Nb is 0.5%, the content of O is 0.11%, the content of Fe is 0.6%, and the content of Si is 0.015%.

[0105] Comparative Example 6

[0106] The difference from Example 1 is that the content of Sn in the zirconium alloy ingot is 0.5%, the content of Nb is 0.5%, the content of O is 0.11%, the content of Fe is 0.3%, and the content of Si is 0.03%.

[0107] Test Example 1

[0108] The strips prepared in Examples 1 to 3 and Comparative Example 1 were subjected to mechanical property tests at room temperature and 315°C, respectively, and the test methods were based on ASTM E8 / E8M and ASTM E21. The test results are shown in Table 1 below. UST is tensile strength, YS is yield strength, and E is elongation after break.

[0109] Table 1:

[0110]

[0111]

[0112] From Table 1, it can be seen that the resistance strength and elongation of Examples 1 to 3 are basically the same, and the yield strength ratio is significantly lower than that of the comparative example, which shows that the examples have improved the organizational properties of the material and reduced the yield strength ratio by optimizing the hot processing process, and improved the material punching forming performance while ensuring the material strength. Comparative Example 2 has a relatively low tensile strength due to the low Sn content; Comparative Example 3 has a relatively low tensile strength due to the low Nb content, which weakens the strengthening effect; Comparative Example 4 has a significantly improved strength due to the high O content, but the processing performance is deteriorated, which is not conducive to the punching forming of the finished strip; Comparative Example 5 has a significantly lower elongation due to the high Fe element, and the processing plasticity is reduced, and edge crack defects are prone to occur during the processing; Comparative Example 6 has a relatively high strength due to the high Si element, but the elongation is reduced and the plasticity is deteriorated.

[0113] Test Example 2

[0114] The strips prepared in Examples 1 to 3 and Comparative Example 1 were subjected to corrosion performance tests, and the test process was as follows: three samples were randomly selected from the strips, placed in 400±3°C, 10.3±0.7MPa high temperature steam for 72 to 80 hours, and the corrosion weight gain was tested and the appearance after corrosion was observed. The test results are shown in Table 2.

[0115] Table 2:

[0116]

[0117] As can be seen from Table 2, the weight gain after corrosion and the appearance after corrosion of Examples 1 to 3 and Comparative Examples 4 to 6 are basically the same, indicating that the corrosion performance of the finished strips prepared by the two is equivalent, and both meet the technical requirements of Zr-Sn-Nb strips for nuclear power. This is mainly because both processes can strictly control the hot working and heat treatment process after quenching, and the second phase of the finished product is finely dispersed, giving full play to the advantages of good corrosion resistance of Zr-Sn-Nb alloy. Comparative Example 2 has a low Sn content and Comparative Example 3 has a low Nb content, so the corrosion resistance is inferior to that of other examples.

[0118] Test Example 3

[0119] The grain size of the strips prepared in Examples 1 to 3 and Comparative Example 1 was tested in accordance with ASTM E112-13. The test results are shown in Table 3.

[0120] Table 3:

[0121] Grouping Horizontal Vertical Example 1 12.0 12.0 Example 2 11.5 11.5 Example 3 11.5 11.5 Comparative Example 1 11.5 11.5 Comparative Example 2 11.5 11.5 Comparative Example 3 11.5 11.5 Comparative Example 4 11.5 11.5 Comparative Example 5 11.5 11.5 Comparative Example 6 11.5 11.5

[0122] It can be seen from Table 3 that the total processing deformation of the embodiment and the comparative example is basically the same, and the transverse and longitudinal grain sizes of the finished strips are equivalent, indicating that the finished strips prepared by both are in a fine and uniform recrystallized state, and the grain sizes can meet the technical requirements of Zr-Sn-Nb strips for nuclear power.

[0123] Test Example 4

[0124] The texture factor of the strips prepared in Examples 1 to 3 and Comparative Example 1 was tested using the EBSD (backscattered electron diffraction) method. The test results are shown in Table 4.

[0125] Table 4:

[0126] Grouping Normal Fn Horizontal Ft Vertical F1 Example 1 0.595 0.311 0.094 Example 2 0.588 0.315 0.097 Example 3 0.589 0.314 0.097 Comparative Example 1 0.663 0.251 0.085 Comparative Example 2 0.687 0.211 0.103 Comparative Example 3 0.693 0.203 0.104 Comparative Example 4 0.709 0.199 0.092 Comparative Example 5 0.682 0.197 0.121 Comparative Example 6 0.707 0.211 0.081

[0127] It can be seen from Table 4 that compared with comparative examples 1 to 6, the normal texture factor of embodiments 1 to 3 is reduced and the transverse texture factor is increased, which indicates that the embodiments have increased the rolling deformation, weakened the base surface texture, improved the transverse texture, improved the microstructure and properties of the finished strip, and improved the punching formability of the finished strip through the optimization of the hot working process.

[0128] Test Example 5

[0129] The hot-rolled annealed strip and the finished strip prepared in Example 1 were subjected to metallographic examination and texture inspection, respectively. The inspection results are as follows: Figures 2 to 5 As shown, the texture of the finished strip prepared in Comparative Example 1 was tested, and the test results are as follows Figure 6 shown.

[0130] according to Figure 2 and Figure 3 It can be seen that the hot-rolled coil is annealed at a temperature of 580-650°C for 2-6 hours, and homogenized until the grain size of the coil is above level 8.0. The coil after hot-rolling annealing is subjected to 60%-95% cold rolling deformation, and the grain structure is further refined. After finished product annealing, a fine and uniform recrystallized structure is finally obtained.

[0131] according to Figure 4 and Figure 5 It can be seen that the rolling deformation is increased by optimizing the hot working process. After annealing, the hot-rolled coil presents a typical bimodal texture, which provides a good organizational basis for cold deformation. During the cold deformation process, the zirconium alloy is restricted by its close-packed hexagonal crystal structure, the basal texture increases, and the transverse texture decreases.

[0132] according to Figure 5 and Figure 6 It can be seen that the embodiment increases the rolling deformation by optimizing the hot working process, which is beneficial to weakening the base surface texture, improving the transverse texture, improving the microstructure and properties of the finished strip, and improving the stamping formability of the strip.

[0133] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0134] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0135] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A zirconium alloy ingot, characterized in that: In terms of mass content, the zirconium alloy ingot has a Sn content of 0.5% to 1.0%, a Nb content of 0.2% to 1.1%, an O content of 0.08% to 0.14%, a Fe content of 0.2% to 0.5%, and a Si content of 0.01% to 0.02%.

2. A method for preparing high-quality Zr-Sn-Nb alloy strip for nuclear power, characterized in that: Utilizing the zirconium alloy ingot according to claim 1, comprising the following steps: (a) processing a zirconium alloy ingot into a slab by free forging; (b) directly β-phase quenching the slab and removing the surface oxide scale, and then hot-rolling the slab to a continuous length of more than 40 m to obtain a hot-rolled slab; (c) bending the hot-rolled slab into a coil and subjecting it to homogenization treatment until the grain size of the coil is above 8.0 and the transverse texture factor is above 0.35; (d) mechanically polishing and chemically polishing the tape coil obtained in step (c) to a surface roughness of less than 1.6 μm, and bending the tape coil into a coil at room temperature; (e) unwinding the strip coil obtained in (d), cold rolling it to obtain a seamless strip, and degreasing and annealing it to obtain a finished strip.

3. The method according to claim 2, characterized in that In step (a), the free forging adopts a two-fire forging process, the forging temperature is 850-1100° C., and the holding time is 60-240 minutes.

4. The method according to claim 2, characterized in that In step (a), the slab has a thickness of 80 to 150 mm and a length of 2000 to 6000 mm.

5. The method according to claim 2, characterized in that In step (b), the temperature of the β-phase quenching is 50-120° C. higher than the β-phase transformation temperature of the zirconium alloy.

6. The method according to claim 2, characterized in that In step (b), hot rolling is carried out by a hot rolling mill, the hot rolling temperature is 550-700° C., the hot rolling deformation is 75%-95%, and the slab is hot rolled once through 8-15 passes to a thickness of 3-7 mm.

7. The method according to claim 2, characterized in that In step (c), the homogenization treatment is carried out at 580-650° C. for 2-6 hours, and the temperature of the homogenization treatment is lower than the hot rolling temperature.

8. The method according to claim 2, characterized in that In step (e), the cold rolling deformation amount during the cold rolling process is 60% to 95%, the rolling speed is 30 to 120 m / min, and the pass deformation amount is 5% to 20%.

9. The method according to claim 2, characterized in that In step (e), the grain size of the finished strip is above level 10.0, and the transverse texture factor is above 0.

30.

10. A high-quality Zr-Sn-Nb alloy strip for nuclear power, characterized in that: The method is prepared by any one of claims 2 to 9.

11. Use of the high-quality Zr-Sn-Nb alloy strip prepared by the method according to any one of claims 2 to 9 or the high-quality Zr-Sn-Nb alloy strip for nuclear power according to claim 10 in nuclear fuel assemblies.

Citation Information

Cited By

  • High-strength corrosion-resistant Zr-Sn alloy plate for heavy water reactor drainage pipe and preparation method of high-strength corrosion-resistant Zr-Sn alloy plate

    CN121023302A